2018
DOI: 10.3892/mmr.2018.9096
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑199b promotes cell proliferation and invasion in Wilms' tumour by directly targeting Runt‑related transcription factor 3

Abstract: Emerging evidence has demonstrated that the deregulation of microRNAs (miRNAs) contributes to Wilms' tumour (WT) malignant progression. Therefore, identifying the essential miRNAs for WT onset and progression may be a promising therapeutic method for patients with this disease. Dysregulation of miRNA‑199b (miR‑199b) serves significant roles in various types of human cancer. However, its expression patterns, possible functions and associated mechanisms in WT are largely unknown. In the present study, the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Thus, this type of miRNAs may exert pivotal role in modulation of chemotherapy response in GCs. miR-199b expression is upregulated in Wilms' tumor, and miR-199b can directly target RUNX3 to promote Wilms' tumor progression, indicating that the miR-199b/RUNX3 axis represents a potential target for Wilms' tumor treatment [25]. miR-199b also serve as an oncogene in osteosarcoma (OS).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this type of miRNAs may exert pivotal role in modulation of chemotherapy response in GCs. miR-199b expression is upregulated in Wilms' tumor, and miR-199b can directly target RUNX3 to promote Wilms' tumor progression, indicating that the miR-199b/RUNX3 axis represents a potential target for Wilms' tumor treatment [25]. miR-199b also serve as an oncogene in osteosarcoma (OS).…”
Section: Discussionmentioning
confidence: 99%
“…Although they have a low molecular weight, they play key roles at the transcriptional level of human cells, regulating several important biological functions, such as tumor cell proliferation, invasion and migration (11). A number of studies have demonstrated that microRNAs are abnormally expressed in different tumors, and they act as tumor suppressors or tumor-promoting factors (12,13). Yang and Guo reported that miR-3147 can participate in the epithelial-to-mesenchymal transition of VSCC cells by inhibiting Smad4 (14).…”
Section: Introductionmentioning
confidence: 99%